Closed chain rehabilitation after tennis injuries in the lower and upper extremity - Kibler, W. B. (2001)
Restoration of function after lower or upper extremity injury involves both restoration of anatomic integrity and restoration of the physiological and biomechanical alterations in flexibility, joint motion, strength, muscle activation, and force and power development that may be associated with the injury. Common examples include gluteus medius weakness in ankle sprains and following anterior cruciate ligament injury, hip flexor tightness and hip extensor weakness in patellofemoral pain, lumbar extension weakness in both lower and upper extremity injury, scapular dyskinesis in labral injury, and glenohumeral internal rotation deficit in shoulder pain. Closed chain exercise protocols have been advocated to achieve superior functional results because they more closely simulate normal functional positions and motions, protect healing or injured tissues from tensile strains, and allow more normal proprioceptive feedback. In this manner, they help achieve the goals of more normal physiological and biomechanical restoration while protecting the anatomic repair. Closed chain protocols have been associated with "accelerated" lower extremity rehabilitation, and have shown good results. These exercises start with the foot on the ground, and allow load application through this stable base up the leg to the hip. The compression forces decrease shear at the knee joint, while stimulating co-contraction muscle activation to stabilize the knee. Exercises commonly used include standing weight shifts, with support on a table, progressing from 2 leg stance to 1 leg stance; standing squats, progressing from half to full squat, then to 1 leg squats; step up/step down, both in frontal and lateral motions; trunk/leg rotations; squats or stance on a trampoline or other unstable surface, and lunges. These should always be done from a starting position of hip extension, slight hip valgus, and trunk balance over the leg. This assures proper kinetic chain balance and control of the proximal musculature which play a major role in activation and control of the entire lower extremity muscle activation and strength development. Upper extremity closed chain protocols are not as widely used, but can be shown to be beneficial. These exercises establish a stable scapular base of muscle origin, restore the normal coupled motion of the scapula with the arm, re-establish the co- contraction force couples for shoulder joint stability, and restore the kinetic chain sequence of activation and motion which starts from the ground and proceeds to the arm. Exercises include hip extension/trunk extension/scapular retraction coupled activations; scapular clock exercises, "low row" exercises, with scapular extension/shoulder extension; "wall washes" involving axial load through placing the hand on the wall and moving it in vertical and diagonal motions; and punches, moving the arm in various planes with varying types (weights, tubing) of resistance and varying speeds, to challenge different muscle groups. Closed chain protocols can be of benefit to accelerate the rehabilitation process. Care must be taken to include all muscle groups in the protocols, because closed chain activations sometimes do not maximally activate certain muscles, such as vastus medialis obliquus (VMO), lower trapezius, and supraspinatus. Facilitation of these activations may be accomplished by starting in the closed chain positions and then progressively "unmasking" the target muscle by decreasing supporting muscle use. The VMO may be unmasked by starting from a flexed posture at the hip, while supraspinatus may be unmasked by increasing the amount of diagonal arm activity or increasing the speed of the movement.